Exploring the status of an urban coral and the presence of potential probiotic traits in culturable bacteria (2024)
Improving the availability of new sources of probiotics is essential to continue implementing alternative solutions to improve coral health; one such source is urban corals. However, little is known about urban coral’s health status and whether they can harbor bacteria exhibiting probiotic traits. Here, we explored the status of the urban coral Madracis auretenra and the presence of probiotic traits in its associated culturable bacteria. After assessing ecological attributes, we observed a similar abundance (cover %) when comparing patches of M. auretenra occurring in both an urban site and a marine protected area. The urban patch also exhibited a high abundance of vibrios in coral tissues and signs of ecosystem deterioration. However, this patch showed a “good” health index condition; so, we hypothesized the presence of beneficial bacteria. We isolated 132 bacterial strains from this healthy urban M. auretenra. These bacteria were affiliated with 11 genera, including Vibrio, Shewanella, Bacillus, Exiguobacterium, Priestia, and Niallia, among others. Screenings revealed the predominant presence of potential probiotic traits such as catalase, antiQS, and the production of siderophores activities among the bacterial isolates. We proposed a list of 24 bacterial isolates as probiotic precandidates that jointly exhibited three or more of these traits, among which the Vibrio and Bacilli strains stand out. We provide insights into the health status of this urban coral and its potential as a source of bacteria exhibiting potential probiotic traits.